Radiological results and clinical patient outcome after implantation of a hydraulic expandable vertebral body replacement following traumatic vertebral fractures in the thoracic and lumbar spine: A 3-year follow-up - Kreinest, Michael; Schmahl, Dorothee; Grützner, Paul Alfred; Matschke, Stefan (Spine, 2017)
STUDY DESIGN: A prospective monocentric study. OBJECTIVE: The aim of the current study was the analysis of patient outcome and radiological results 3 years after implantation of a hydraulic expandable vertebral body replacement (VBR) system.SUMMARY OF BACKGROUND DATA: Around 70% to 90% of all traumatic spinal fractures are located in the thoracic and lumbar spine. Dorso-ventral stabilization is a frequently used procedure in traumatic vertebral body fracture treatment. VBR systems can be used to bridge bony defects. In the current study, a new VBR expanded by water pressure with adjustable endplates is used. METHODS: All patients who suffered a singular traumatic fracture to a thoracic or lumbar vertebral body (Th 5-L 5) in the period from November 2009 to December 2010 and (i) underwent dorsal instrumentation and (ii) afterwards received the implantation of a hydraulic VBR were included in this study. The clinical outcome (visual analogue scale [VAS] spine score, questionnaire) and radiological findings (sagittal angle, implant subsidence, and implant position) 3 years after implantation were analyzed. RESULTS: The follow-up was successful for n=47 patients (follow-up rate: 89%). Most of the patients (n=40) were "generally/very satisfied" with their outcome. The mean rating of the VAS spine score was 65.2±23.1 (range: 20.5-100.0). The analysis of the radiological data showed an average subsidence of the implants of 1.1±1.2mm (range 0.0-5.0mm). After the initial operation, the local sagittal angle remained stable in the follow-up 3 years later both for the thoracic spine and lumbar spine. Furthermore, no change in the implant's position was observed. CONCLUSION: The implantation of a hydraulically expandable VBR allows a permanent stable fixation after traumatic fractures of the thoracic and lumbar spine. LEVEL OF EVIDENCE: 2.
Gesehen am 17.04.2018